MODELING HIDDEN NODES COLLISIONS IN WIRELESS SENSOR NETWORKS: ANALYSIS APPROACH - A. Sjamsjiar Rachman; Wirawan Wirawan; Gamantyo Hendrantoro (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2010)
This paper studied both types of collisions. In this paper, we show that advocated solutions for coping with hidden node collisions are unsuitable for sensor networks. We model both types of collisions and derive closed-form formula giving the probability of hidden and visible node collisions. To reduce these collisions, we propose two solutions. The first one based on tuning the carrier sense threshold saves a substantial amount of collisions by reducing the number of hidden nodes. The second one based on adjusting the contention window size is complementary to the first one. It reduces the probability of overlapping transmissions, which reduces both collisions due to hidden and visible nodes. We validate and evaluate the performance of these solutions through simulations.